Prulifloxacin Effectiveness in Moderate-to-Severe Acute Exacerbations of Chronic Bronchitis: Α Noninterventional, Multicentre, Prospective Study in Real-Life Clinical Practice—The "AIOLOS" Study. (26th May 2021) - Gourgoulianis, Konstantinos; Ruggieri, Alessandro; Vecchio, Alessandra del; Calisti, Fabrizio; Comandini, Alessandro; Esposito, Giovanna; Di Loreto, Giorgio; Tzanakis, Nikolaos
Abstract : Real-world evidence regarding the effectiveness of prulifloxacin in the treatment of acute exacerbations of chronic bronchitis (AECB) is limited. Therefore, this study aimed to assess the rates and time to symptom improvement and resolution in patients with moderate-to-severe AECB who were given prulifloxacin in the routine care in Greece. This observational, prospective study, conducted in 15 hospital-based clinics across Greece, enrolled outpatients >40 years old, with moderate-to-severe AECB, for whom the physician had decided to initiate treatment with prulifloxacin. Data were collected at prulifloxacin onset (baseline), 7–10 days after baseline, and at least 28 days after therapy completion. Between 23 November 2015 and 27 January 2018, 305 patients (males: 76.4%; mean (standard deviation) (SD) age: 69.7 (9.8) years; Anthonisen type I/II: 94.8%; chronic bronchitis duration >10 years: 24.9%) were consecutively enrolled. At baseline, >80% had increased sputum volume, cough, dyspnoea, and sputum purulence. Prulifloxacin improved symptoms in 99.7% of the patients after a mean (SD) of 5.47 (3.57) days, while symptoms fully recovered after a mean (SD) of 10.22 (5.00) days in 95.4%. The rate of adverse events related to prulifloxacin was 1.3% (serious: 0.7%). In the routine care in Greece, prulifloxacin was highly effective in moderate-to-severe AECB, while displaying a predictable safety profile.